2021
DOI: 10.1371/journal.pone.0248099
|View full text |Cite
|
Sign up to set email alerts
|

Medical face masks offer self-protection against aerosols: An evaluation using a practical in vitro approach on a dummy head

Abstract: Since the appearance of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the question regarding the efficacy of various hygiene measures and the use of personal protective equipment (PPE) has become the focus of scientific and above all public discussion. To compare respirators, medical face masks, and cloth masks and determine if it is recommendable to wear face masks to protect the individual wearer of the mask from inhaling airborne particles, we challenged 29 different masks with aerosols and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 22 publications
0
21
0
1
Order By: Relevance
“…We have shown that the quality of filtration of different masks varies by mask, and by aerosol particles at different size. To the best of our knowledge, this is not the “first experiment” to explore the FEs of different mask types ( Whiley et al, 2020 , Leung et al, 2020 , Pan et al, 2021 , Sterr et al, 2021 , Ueki et al, 2020 ). But this study shows that FE decreases significantly as the wearing time or respiratory volume increases.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that the quality of filtration of different masks varies by mask, and by aerosol particles at different size. To the best of our knowledge, this is not the “first experiment” to explore the FEs of different mask types ( Whiley et al, 2020 , Leung et al, 2020 , Pan et al, 2021 , Sterr et al, 2021 , Ueki et al, 2020 ). But this study shows that FE decreases significantly as the wearing time or respiratory volume increases.…”
Section: Discussionmentioning
confidence: 99%
“…Largest differences were observed between the items "mouth feels dry" and "lips feel dry", most probably as wearing face masks is likely to change the breathing pattern. However, airflow and breathing resistance vary between different face masks based on mask material and proportion of leakage: KN95-/FFP2-masks and community masks were reported to result in higher breathing resistance than medical face masks, leading to potential leakage [15]. Dry mouth is most probably perceived due to a change of the breathing pattern from nasal to oral breathing while wearing masks [16].…”
Section: Discussionmentioning
confidence: 99%
“…Different aspects of the pharmacological and toxicological interactions of drugs should also be considered in relation to many other complex factors and sectors, which are continuously identified in relation to the progress of COVID-19 including molecular, multi-genomic and other effects, as well as other methods for trying to curb the COVID-19 [128][129][130][131][132].…”
Section: Pharmacological and Toxicological Aspects Of Drugs Against Covid-19mentioning
confidence: 99%